2023
DOI: 10.1002/capr.12617
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and obstacles to therapeutic alliance among patients with anorexia nervosa: A qualitative dyadic research

Abstract: ObjectiveStudies indicate a significant challenge for therapists in forming a therapeutic alliance (TA) with patients coping with anorexia nervosa (AN). While TA is a significant predictor of treatment outcomes, and AN treatment has low success rates, little is known about factors that affect the formation of an alliance and its quality in the treatment of AN. This study aimed at examining the factors associated with alliance formation, as perceived by patient–therapist dyads throughout AN therapy.MethodsA tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The findings align with broader recognition that outcome research in the field of EDs is dramatically biased towards psychopathological dysfunction, on the assumption that mental health is predicated on the absence of illness rather than the presence of psychological wellness (Fava and Tomba, 2009;de Vos et al, 2018). Additionally, evidence relating the therapeutic alliance to ED treatment outcome are of limited clinical use without a better understanding of the facilitators or barriers to therapeutic alliance formation in ED patients (Lev Ari et al, 2024).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The findings align with broader recognition that outcome research in the field of EDs is dramatically biased towards psychopathological dysfunction, on the assumption that mental health is predicated on the absence of illness rather than the presence of psychological wellness (Fava and Tomba, 2009;de Vos et al, 2018). Additionally, evidence relating the therapeutic alliance to ED treatment outcome are of limited clinical use without a better understanding of the facilitators or barriers to therapeutic alliance formation in ED patients (Lev Ari et al, 2024).…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, despite the mixed findings on ED samples, we hypothesized that the early therapeutic alliance would significantly predict clinically significant and reliable symptom reduction (Zaitsoff et al, 2015;Graves et al, 2017). Furthermore, in line with studies showing an indirect effect of the therapeutic alliance on therapy outcome (Baier et al, 2020) and the potential relevance of ED patients' individual characteristics in determining this association (Prusiński, 2022;Lev Ari et al, 2024), we expected that the therapeutic alliance would mediate the relationship between PWB dimensions and overall symptomatic change.…”
Section: Present Studymentioning
confidence: 64%
See 2 more Smart Citations
“…There is a poor treatment retention rate for ED patients (Satir et al, 2011; Sly et al, 2013), which can make it difficult to form a long-term alliance and may be a result of poor alliance formation in itself. It can also be difficult for ED patients to engage in a meaningful relationship with their therapists, whether due to a fear of reexperiencing disappointment and pain in intimate relationships (Ari et al, 2024) or interpersonal difficulties that are characteristic of EDs interfering (Constantino et al, 2005). Oyer et al (2016) demonstrated that both therapists and patients find a lack of attunement to patient needs to be detrimental to the therapeutic alliance with ED patients, though this lack of attunement may be common in this population as patients are particularly resistant to change (Abbate-Daga et al, 2013) and often experience their EDs as egosyntonic (Gagnon-Girouard et al, 2019).…”
mentioning
confidence: 99%